The assistant lighting designer's toolkit - McMills, Anne E. (New York, NY : Routledge, 2022)
"The ground-breaking text that took the lighting world by storm returns in its second edition, unlocking the insider secrets and proven, time-tested methods to succeed as a professional assistant lighting designer. This definitive guide outlines, step-by-step, the daily challenges that assistant lighting designers face during every phase of production, and the solutions for overcoming them. Furthermore, intermingled among the highly detailed paperwork techniques and essential procedures, top industry professionals reveal tips for success in this challenging career. This fully updated second edition features: All new advice, real-world stories, and current paperwork examples from over 120 working professionals. Updated industry practices with case studies from the professionals themselves, such as how to create a video network to record previews for the lighting department; how much printing is done in an increasingly paperless world; how to produce a set electrics package; and how the industry interfaces with cutting-edge technology like remote followspots and previsualization software. New lifestyle tips for travelling abroad, negotiating contracts, and dealing with stressful situations. The Assistant Lighting Designer's Toolkit, the most trusted authority on assisting in the lighting world, equips budding assistant lighting designers and students studying lighting design with the insider knowledge they need to achieve the successful career that they have always wanted - whether choosing assisting as a career or as a stepping-stone towards design. Within these pages are the industry secrets rarely taught in school!"--
Foreword / by Ken Billington -- Understanding assisting -- The tools required -- Production personnel -- Unions -- Design prep -- Load-in -- Tech -- Previews and performances -- Pre-production paperwork -- Tech process paperwork -- U.S.-based employment opportunities -- Working internationally -- Working in industries outside of theatre -- Working as an independent contractor.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Access is available to the Yale community.
Keywords: Stage lighting